Effects of Four Teaching Strategies on the Academic Performance of Senior High School Students - Libo-on, Joefel; Perez, Jeannie (Romblon State University Research Journal, 2022)
Determining the effects of four teaching strategies on the academic performance of senior high school students was the main objective of this study. The quasi-experimental design, specifically the equivalent pretest-posttest design was used. A grade-11 class was divided into four sections, the three sections served as the experimental classes subjected to game-based, outcome-based, and technology-based teaching strategies, and one section served as the control group who undertook the traditional teaching method. Results showed that all groups were at a "satisfactory" level of performance before the treatment. Although the means of the experimental groups increased a little than that of the control group after the treatment, still all groups were at a "satisfactory” level. Before treatment, all groups were comparable, but difference was observed after the treatment. Improvement from pretest to posttest performance of the experimental groups and control group was found for outcome-based and traditional teaching methods. However, no significant statistical differences were found between the pretest-posttest for the other pairings. The utilization of outcome-based teaching strategies is an effective way of enhancing the level of performance of students in Mathematics compared to other teaching strategies. In the mean gain scores, statistical significance existed in the mathematics performance of the experimental groups and control group. Students exposed to outcome-based strategy performed better than those students who are exposed to other teaching strategies; while game-based, outcome-based, technology-based, and traditional teaching methods also improved the mathematics performance of students.